2021
DOI: 10.1126/sciadv.abh4181
|View full text |Cite
|
Sign up to set email alerts
|

Heart neurons use clock genes to control myocyte proliferation

Abstract: Neurons regulate cardiomyocyte proliferation through clock genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 75 publications
(121 reference statements)
0
15
0
Order By: Relevance
“…Neural connections are established during late embryonic and early postnatal development by a co-maturation system 10, 11 where innervation patterning and maturation relies on signals from a variety of cardiac tissues 12, 13 . Interestingly, sympathetic nerves have been demonstrated to mediate the postnatal transition of cardiomyocytes from hyperplasia to hypertrophy 14 and cardiomyocyte size 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Neural connections are established during late embryonic and early postnatal development by a co-maturation system 10, 11 where innervation patterning and maturation relies on signals from a variety of cardiac tissues 12, 13 . Interestingly, sympathetic nerves have been demonstrated to mediate the postnatal transition of cardiomyocytes from hyperplasia to hypertrophy 14 and cardiomyocyte size 15 .…”
Section: Introductionmentioning
confidence: 99%
“…This is nicely illustrated in a recent study, which demonstrated sympathetic neurons can influence heart development via clock genes to regulate myocyte proliferation. Here, Tampakakis et al (2021) inhibited NGF in vascular smooth cells, which resulted in impaired sympathetic innervation in the heart and reduced norepinephrine release. Interestingly, this was associated with proliferating cardiac myocytes and enlarged hearts that was directly related to downregulation in clock genes ( Per1/Per2 ).…”
Section: Discussionmentioning
confidence: 97%
“…For example, it has been shown that the circadian clockwork can control cell-division cycles in the liver directly, 31 and in the heart, it has been shown that cardiac neurons use clock genes to control myocyte proliferation. 32 One limitation of our study is that the bulk RNA sequencing used allows limited insight into the transcriptome of single cells, even less into differentially expressed genes in rare cells. However, our study suggests that changes to the cardiac environment, for example, improved circadian entrainment attributable to exercise or exercise-induced cardiac cell cycle activity, might help to facilitate cytokinesis in a few cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%